299 Treatment with prostaglandin F2α and an intravaginal progesterone insert in advance of gonadotropin-releasing hormone enhances response to estrus synchronization in mature beef cows. (5th December 2019) - Bonacker, Rachael C; Stoecklein, Katy S; Ketchum, Jaclyn N; Knickmeyer, Emma R; Locke, James William C; Poock, Scott E; Thomas, Jordan M
Abstract: An experiment was designed to evaluate the effect of treatments in advance of gonadotropin-releasing hormone (GnRH; 100μg gonadorelin) administered at the start of estrus synchronization. We hypothesized that administration of prostaglandin F2α (PG; 500μg cloprostenol) followed by treatment with an intravaginal progesterone-releasing insert (CIDR; 1.38g progesterone) would result in increased follicle size at GnRH, thereby enhancing response to GnRH and overall response to estrus synchronization. Postpartum suckled beef cows (n = 183) in two locations were assigned to one of five treatments based on age, days postpartum, and body condition score. Treatments (Figure 1) were designed as a two-by-two factorial with a control (Treatment 1). Treatments 2–5 received a CIDR insert from Day -17 to Day -10, with (Treatments 2 and 3) or without (Treatments 4 and 5) administration of PG coincident with CIDR insertion on Day -17. Coincident with GnRH administration on Day -10, CIDR inserts were either removed (Treatments 2 and 4) or remained in place until Day -3 (Treatments 3 and 5). On Day -3, estrus detection aids were applied and a representative subset of cows in each treatment were fitted with estrus detection transmitters. Blood samples were collected on Days -27, -17, -10, -3, and 0 for determination of serum estradiol and/or progesterone concentrations via radioimmunoassay. For a representative subset of cows (n = 111), transrectal ovarian ultrasound was performed to assess ovarian follicle size and presence of corpora lutea on Days -17, -10, -3, and 0. Treatment with PG and CIDR in advance of GnRH resulted in improvements (P < 0.05) in several response variables, including follicle size on Day -17 and estrous response prior to AI. Results support the hypothesis that administration of PG and treatment with a CIDR for 7 d prior to GnRH improves likelihood of GnRH response and enhances response of mature cows to estrus synchronization.